2008
DOI: 10.1016/j.tins.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Origin and function of olfactory bulb interneuron diversity

Abstract: In adult rodents, subventricular zone (SVZ) astrocytes (B cells) function as primary progenitors in the generation of new neurons that migrate to the olfactory bulb (OB), where they differentiate into multiple types of interneurons. It has been generally considered that individual adult SVZ stem cells are capable of generating different types of neurons and glial cells. However, recent studies indicate that these adult SVZ primary progenitors are heterogeneous and predetermined to generate specific types of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
339
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(347 citation statements)
references
References 71 publications
8
339
0
Order By: Relevance
“…In addition, we have shown that ectopic expression of NeuroD1 is sufficient to induce instant and widespread neuronal differentiation in the periventricular area, a region that is specialized in the maintenance of stem cells (4,5,30). Overexpression of the determination factor Pax6 did not induce a comparable phenotype, demonstrating the specificity of the observed phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, we have shown that ectopic expression of NeuroD1 is sufficient to induce instant and widespread neuronal differentiation in the periventricular area, a region that is specialized in the maintenance of stem cells (4,5,30). Overexpression of the determination factor Pax6 did not induce a comparable phenotype, demonstrating the specificity of the observed phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Here, stem cell populations first located in the ventricular zone and after the establishment of an ependymal layer positioned in subventricular zone (SVZ) generate migratory neuroblasts throughout life (4). These perform long-distance chain migration via the rostral migratory stream (RMS) into the olfactory bulb (OB), where they migrate into the granule cell layer (GCL) and the glomerular layer (GL) to differentiate into GABA-and dopaminergic neurons (4,5). Thus, in this system, generation of neurons is permanent and the consecutive steps in the neurogenic sequence are spatially separated.…”
mentioning
confidence: 99%
“…Along with the dentate gyrus (DG) of the hippocampal formation, the olfactory bulb (OB) is a region of the mammalian brain in which there is a continued supply of newly generated neurons (Abrous et al, 2005;Lledo et al, 2008). Olfactory adult-born neurons originate from the periventricular region, and then migrate tangentially through the rostral migratory stream to reach the OB.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the subependymal zone (SEZ) harbors aNSCs, which give rise to neuroblasts that migrate tangentially along the rostral migratory stream (RMS) to the OB. There, the neuroblasts migrate radially and differentiate into various types of interneurons populating both the granule cell layer (GCL) and the glomerular layer (17,18). We therefore adapted the RABV-based monosynaptic tracing technique to target adult-generated neurons for primary RABV infection.…”
mentioning
confidence: 99%